EXPERIMENT BASED WORK SHEET DEVELOPMENT ON FACE SERUM BASED ON MILK KEFIR AND AVOCADO FRUIT EXTRACT (PERSEA AMERICANA) (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to describe the appearance of the worksheet (LK) and analysis of the results of the validation test worksheet based on experiments on the manufacture of facial serum made from kefir whey and avocado extract. Worksheets were made using the design based research (DBR) method, by adapting the ADDIE Instrument model used, namely validation test sheets, worksheet grids, worksheets, and validation questionnaires filled out by the validator. The preparation of this Lk includes the stages of concept analysis in advanced natural substance chemistry courses, analysis of the research literature on facial serum making, analysis of steps in LK. So as to produce a product in the form of LK. The results of the validation test were processed using the correlation technique (r) which compared rcount with criticality. From the research, the mean count was 0.77 which was categorized as quite high. Thus it can be said that the worksheet is valid and is used as a medium for learning the chemistry of natural materials in cosmeseutical concepts.